The Importance of Magnesium in Clinical Healthcare - Gerry K. Schwalfenberg; Stephen J. Genuis (Scientifica)
The scientific literature provides extensive evidence of widespread magnesium deficiency and the potential need for magnesium repletion in diverse medical conditions. Magnesium is an essential element required as a cofactor for over 300 enzymatic reactions and is thus necessary for the biochemical functioning of numerous metabolic pathways. Inadequate magnesium status may impair biochemical processes dependent on sufficiency of this element. Emerging evidence confirms that nearly two-thirds of the population in the western world is not achieving the recommended daily allowance for magnesium, a deficiency problem contributing to various health conditions. This review assesses available medical and scientific literature on health issues related to magnesium. A traditional integrated review format was utilized for this study. Level I evidence supports the use of magnesium in the prevention and treatment of many common health conditions including migraine headache, metabolic syndrome, diabetes, hyperlipidemia, asthma, premenstrual syndrome, preeclampsia, and various cardiac arrhythmias. Magnesium may also be considered for prevention of renal calculi and cataract formation, as an adjunct or treatment for depression, and as a therapeutic intervention for many other health-related disorders. In clinical practice, optimizing magnesium status through diet and supplementation appears to be a safe, useful, and well-documented therapy for several medical conditions.